The Effect of Interactive Multimedia Use on Students' Learning Motivation in Subjects History of Islamic Culture at MTs PAB-1 Helvetia - Rizka Lathifah Husna; Hasrian Rudi Setiawan (Al-Ulum: Jurnal Pendidikan Islam, 2021)
This study aims to determine whether there is an effect of using interactive multimedia on students' learning motivation. This type of research is experimental quantitative research, the subject of this research is students in class VII A MTs PAB-1 Helvetia. Data collection techniques used by researchers are interviews, observation and documentation. The data analysis used is quantitative data analysis by calculating the product moment correlation. The results obtained are the influence of the use of multimedia on students' learning motivation in Islamic cultural history subjects at MTs PAB-1 Helvetia, where students' learning motivation in Islamic cultural history subjects at MTs PAB-1 Helvetia, after using interactive multimedia is more increased compared to not using interactive multimedia.Keywords: Interactive Multimedia, Learning Motivation